2003
DOI: 10.1007/bf02867677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of latent iron deficiency on GABA and glutamate neuroreceptors in rat brain

Abstract: Eight weeks of latent iron deficiency in weaned female rats of Sprague Dawley strain maintained on experimental low-iron diet (18-20 mg/kg) did not significantly change the gross bodyweight and tissue weights of brain and liver. Packed cell volume (PCV) and hemoglobin concentration remained unaltered. However, non-heme iron content in liver and brain decreased significantly (p< 0.001 )o The activities of glutamate dehydrogenase, glutamic acid decarboxylase, and GABA-transaminase (GABA-T) in brain decreased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…Most of the co-relational and experimental studies done earlier confirmed the hypothesis that iron deficiency of mild to moderate nature has an adverse effect on congnitive development (3,7). Therefore, it may be logical to suggest that impairment of higher mental function like cognition and learning in humans (5, 13) may be linked to changes in neurotransmitter receptors and consequent signal transduction process in the nervous system (28,29).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Most of the co-relational and experimental studies done earlier confirmed the hypothesis that iron deficiency of mild to moderate nature has an adverse effect on congnitive development (3,7). Therefore, it may be logical to suggest that impairment of higher mental function like cognition and learning in humans (5, 13) may be linked to changes in neurotransmitter receptors and consequent signal transduction process in the nervous system (28,29).…”
Section: Resultsmentioning
confidence: 98%
“…A significant decrease in non heme iron both in liver and brain without changes in hematocrit are observed and they clearly suggest appreciable decrease in content of iron in certain tissue. The significant effects on neurotransmitter receptors during early stages of iron deficiency indicate the deficits in both excitatory and inhibitory pathways of central nervous system (28). The neurotransmitter receptors remain in dynamic equilibrium and their regulation depends on the synthesis, metabolism and various other components in signal transduction cascade.…”
Section: Iron and Neurotransmittersmentioning
confidence: 99%
“…In addition, increased GABA in the brain, including hippocampus, is found in both iron‐deficient anemia (Batra and Seth ; Mittal et al . ; Rao et al . ) and hypoxia (Madl and Royer ), but hippocampal GABA levels in b/b rats were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Kejang terjadi apabila terdapat depolarisasi berlebihan pada neuron dalam sistem saraf pusat dan jika kondisi ini berada pada level yang tetap dan mendapat rangsangan yang kuat seperti demam tinggi (>38 0 C) dan kondisi anemia. 9,11,12 Berdasarkan penelitian yang dilakukan Khanis 13 didapatkan hasil uji statistik menunjukkan adanya perbedaan pada distribusi kejadian penurunan kadar Hb antara kelompok kasus (kejang demam) dengan kontrol (demam tanpa kejang).…”
unclassified